2019
DOI: 10.1128/jb.00462-18
|View full text |Cite
|
Sign up to set email alerts
|

Making and Breaking of an Essential Poison: the Cyclases and Phosphodiesterases That Produce and Degrade the Essential Second Messenger Cyclic di-AMP in Bacteria

Abstract: Cyclic di-AMP is a second messenger nucleotide that is produced by many bacteria and some archaea. Recent work has shown that c-di-AMP is unique among the signaling nucleotides, as this molecule is in many bacteria both essential on one hand and toxic upon accumulation on the other. Moreover, in bacteria like , c-di-AMP controls a biological process, potassium homeostasis, by binding both potassium transporters and riboswitch molecules in the mRNAs that encode the potassium transporters. In addition to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
160
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 112 publications
(191 reference statements)
0
160
0
5
Order By: Relevance
“…A phylogenetic analysis of the DAC domain of proteins related to DacZ from H. volcanii showed that homologs are presents in almost all euryarchaea and in some bacteria and that, remarkably, structure prediction methods revealed that the N ‐terminal domain has, despite low sequence homology, a fold that resembles the pyruvate kinase C‐terminal alpha/beta domain (PK_C) fold. This domain is also found in DAC representatives of the DacY/CdaZ class (Commichau et al, ; Corrigan & Gründling, ) suggesting that the archaeal DAC classes DacZ and DacY/CdaZ form one large family that is not exclusively found in archaea but also in some bacteria (Figure ). The PK_C fold was initially identified to bind fructose‐1,6‐bisphosphate to allosterically regulate the activity of pyruvate kinase.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…A phylogenetic analysis of the DAC domain of proteins related to DacZ from H. volcanii showed that homologs are presents in almost all euryarchaea and in some bacteria and that, remarkably, structure prediction methods revealed that the N ‐terminal domain has, despite low sequence homology, a fold that resembles the pyruvate kinase C‐terminal alpha/beta domain (PK_C) fold. This domain is also found in DAC representatives of the DacY/CdaZ class (Commichau et al, ; Corrigan & Gründling, ) suggesting that the archaeal DAC classes DacZ and DacY/CdaZ form one large family that is not exclusively found in archaea but also in some bacteria (Figure ). The PK_C fold was initially identified to bind fructose‐1,6‐bisphosphate to allosterically regulate the activity of pyruvate kinase.…”
Section: Discussionmentioning
confidence: 82%
“…Homologs were identified in most euryarchaeal species, but no DACs were identified in crenarchaeota. Proteins of the DacY/CdaZ class, like CdaZ from M. jannaschii , contain an N ‐terminal pyruvate kinase C‐terminal alpha/beta domain (PK_C) (Commichau et al, ; Corrigan & Gründling, ). Remarkably, although the conservation of the N ‐terminal primary sequence of DacZ proteins was very low, homology modeling of the 3D structure of the N ‐termini of these proteins indicated that members of the DacZ class and of the identified bacterial close homologs have a predicted fold similar to the N ‐terminus of members of the DacY/CdaZ class.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations